Carbon Brainprint: quantifying the impact of universities on carbon footprint reduction - Parsons, David; Chatterton, Julia; Clements-Croome, Derek; Elmualim, Abbas; Darby, Howard; Yearly, Tom; Davies, Gareth; Wilson, Ian; Ishiyama, Edward (Cranfield University, 2019)
Universities make tremendous intellectual and technical advances that help other organisations and individuals reduce their own carbon footprints. This is the universities€™ carbon brainprint, and measuring this allows universities to quantify the impact of their research, innovation and knowledge transfer activities on cutting global GHG emissions. It provides further endorsement of the value of investing in universities such as Cranfield to address the challenge of global warming. The initial project developed a set of approaches to estimating the carbon brainprint of an activity, such as research, development, consultancy or training. These were applied to six case studies from Cranfield, Cambridge and Reading Universities, which demonstrated the large impact that higher education institutions can have. A summary of the final report is attached, as well as a summary of each of the six case studies: 1. Ceramic coatings for jet engine turbine blades, Cranfield University and Rolls-Royce. Summary pdf attached; read full case study. 2. Novel offshore vertical axis wind turbines, Cranfield University and Energy Technologies Institute. Summary pdf attached; read full case study. 3. Improved delivery vehicle logistics, Cranfield University and Defra. Summary pdf attached; read full case study. 4. Training for landfill gas inspectors, Cranfield University and Environment Agency. Summary pdf attached; read full case study. 5. Intelligent buildings, University of Reading and HEFCE. Summary pdf attached; read full case study. 6. Optimising defouling schedules for oil-refinery preheat trains, University of Cambridge and EPSRC. Summary pdf attached; read full case study. Additional project outputs are: - The final report at http://dspace.lib.cranfield.ac.uk/handle/1826/6805. - The guidance on calculating brainprints at http://dspace.lib.cranfield.ac.uk/handle/1826/8236. - The 2015 paper €˜Carbon brainprint €“ An estimate of the intellectual contribution of research institutions to reducing greenhouse gas emissions€™ published in Process Safety and Environmental Protection 96, 74€“81. Available at https://doi.org/10.1016/j.psep.2015.04.008. - The 5min35 summary video of the project at https://youtu.be/9GSjDaWO9dQ. The Carbon Brainprint project was highly commended at the 2011 Green Gown Awards in the research category.
Keywords: emissions; greenhouse gases; GHGs; thermal barrier coatings; TBCs; turbine blades; wind turbines; low carbon economy; renewable technologies; VAWT; logistics; landfill sites; methane recovery; intelligent buildings; BEMS; preheat train; Environmental Impact Assessment; carbon; brainprint